2002
DOI: 10.1086/338043
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Pneumococcal Vaccination in Patients with Rheumatoid Arthritis or Systemic Lupus Erythematosus

Abstract: Prevention of bacterial infection, which is a leading cause of morbidity in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), is a priority. However, the safety and immunogenicity of the pneumococcal vaccine in such patients remain controversial. We evaluated the currently available pneumococcal vaccine in patients with RA or SLE. Pneumococcal vaccination was not associated with an appreciable deterioration in any clinical or laboratory measure of disease activity in either group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 22 publications
5
96
0
18
Order By: Relevance
“…Pozzetto et al showed a non-significant increase in CRP 28 days after influenza vaccination while Elkayam et al found no change at all when measuring CRP one month after pneumococcal vaccination [16,17]. According to our observations, increase in CRP is highest 2 days after vaccination and it decreases in the following days.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Pozzetto et al showed a non-significant increase in CRP 28 days after influenza vaccination while Elkayam et al found no change at all when measuring CRP one month after pneumococcal vaccination [16,17]. According to our observations, increase in CRP is highest 2 days after vaccination and it decreases in the following days.…”
Section: Discussionsupporting
confidence: 57%
“…Several vaccines have been used in in vivo models to induce a mild inflammatory response [5,12,14,15]. It is not clear whether influenza and pneumococcal vaccines increase serum CRP concentrations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It seems not to favor the clinical exacerbation of SLE [28]. The response rate of SLE patients to pneumococcal vaccination is only 47%.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 94%
“…Para pacientes que reciben corticosteroides u otros fármacos inmunosupresores, la respuesta a la vacuna 23-valente polisacárida es inferior respecto a controles sanos y restringida a algunos serotipos 81 . La vacunación contra S. pneumoniae no se acompaña de una activación de la enfermedad basal 81 .…”
Section: Vacuna Antineumocóccica En Pacientes Que Reciben Antagonistaunclassified
“…La vacunación contra S. pneumoniae no se acompaña de una activación de la enfermedad basal 81 . La vacuna conjugada 13-valente ofrece protección para aproximadamente 55 a 77% de los serotipos circulantes en el país y la vacuna polisacárida 23 valente para 77 a 95% de los serotipos circulantes en el país 82 .…”
Section: Vacuna Antineumocóccica En Pacientes Que Reciben Antagonistaunclassified